Capture and separation of sulphur hexafluoride - Sosa, Julio E. (2025)
Sulphur hexafluoride (SF6) is a potent greenhouse gas (GHG), possessing the highest global warming potential among commonly monitored GHGs, making its mitigation a critical environmental priority. Numerous porous solid matrices have been developed for SF6 capture; however, large-scale industrial deployment remains hindered primarily by high production costs. In this study, the adsorption and separation of SF6 from SF6/N2 mixtures were investigated using four activated carbon materials (ACs), selected for their low cost, ease of fabrication and suitability for industrial applications. The adsorption equilibria of SF6 and N2 on the four ACs (designated AC1, AC2, AC3 and ACHM) were measured using a gravimetric method at three temperatures: 283, 303 and 323 K. The experimental data were fitted using the Toth adsorption model, which accurately described the system behaviour across both low and high-pressure regions. Additionally, the selectivity of the SF6/N2 was evaluated using Ideal Adsorption Solution Theory (IAST). Among the tested materials, ACHM exhibited superior selectivity of the SF6/N2 mixture, attributed to its high microporosity. Finally, a comparative analysis with materials reported in the literature under industrially relevant conditions highlighted the strong potential of these ACs, particularly in terms of working capacity, selectivity and regeneration capacity.